2008
DOI: 10.1371/journal.pgen.1000316
|View full text |Cite
|
Sign up to set email alerts
|

Gata3 Acts Downstream of β-Catenin Signaling to Prevent Ectopic Metanephric Kidney Induction

Abstract: Metanephric kidney induction critically depends on mesenchymal–epithelial interactions in the caudal region of the nephric (or Wolffian) duct. Central to this process, GDNF secreted from the metanephric mesenchyme induces ureter budding by activating the Ret receptor expressed in the nephric duct epithelium. A failure to regulate this pathway is believed to be responsible for a large proportion of the developmental anomalies affecting the urogenital system. Here, we show that the nephric duct-specific inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
118
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 68 publications
4
118
2
Order By: Relevance
“…During the development of metanephric kidneys, DBA is downregulated in ureteric tip cells (Michael et al, 2007;Grote et al, 2008;Marose et al, 2008). Here, DBA staining performed on metanephric kidney at E15.5 showed that the Lgr4 À/À tips of UB were clearly positive in comparison with the Lgr4 þ/þ tips (n>4) (Fig.…”
Section: Premature Differentiation With Reduced Expression Of Gata3 Amentioning
confidence: 64%
See 4 more Smart Citations
“…During the development of metanephric kidneys, DBA is downregulated in ureteric tip cells (Michael et al, 2007;Grote et al, 2008;Marose et al, 2008). Here, DBA staining performed on metanephric kidney at E15.5 showed that the Lgr4 À/À tips of UB were clearly positive in comparison with the Lgr4 þ/þ tips (n>4) (Fig.…”
Section: Premature Differentiation With Reduced Expression Of Gata3 Amentioning
confidence: 64%
“…Grote et al (2008) have proposed a genetic cascade in which Gata3 acts downstream of b-catenin to prevent premature cell differentiation and they also have reported that Gata3 acts independently of Ret to maintain the cells in an undifferentiated state (Grote et al, 2008 (Fig. 5A).…”
Section: Premature Differentiation With Reduced Expression Of Gata3 Amentioning
confidence: 99%
See 3 more Smart Citations